Occurrences of Lumpy Skin Disease (LSD) in Cattle in Dinajpur Sadar of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
Lumpy skin disease (LSD) is an acute viral disease infectious of cattle and recently emerged very common in Bangladesh causing economic losses. Hence, this study was design to investigate the prevalence of LSD in considering the herd level and some of management status. Thus, a total of 453 sick animals were subjected to study during the period of April 2020 to July 2020 in Dinajpur. LSD was confirmed according to the clinical inspection and microscopic study of skin scraping. The results indicated that the overall prevalence of LSD was 41.06% in cattle. Moreover, the local breed (75%) and young cattle less than one year (64%) were significantly (p